TERMINOLOGY OF FRENCH LINGUISTICS AND LINGUISTIC SYNERGETICS - Kosovych , Olga (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
In the article on the base of the linguistic synergetics concept of G. G. Piotrovsky the problems of French linguistics metalanguage, issues of linguistic terminology are examined. The author emphasizes that the metalanguage of linguistics is a complex phenomenon, which, on the one hand, there are the system relations between terms, on the other one there are general academic vocabulary, words and phrases that are used when describing various aspects of linguistic research. Terminology of linguistics requires a special effort in the studying, because the object-language and metalanguage coincide in terms of expression, that is, have the same substance. The article presents the analysis of the metalanguage state of French linguistics, which is a diachronic interweaving of numerous schools and directions, author’s theories and concepts; the distinctive features of the French linguistic terminology are examined. It is noted that in the semiotic aspect the French linguistic terminology is characterized by the following properties: French linguistic term is a simple or complex sign that in the framework of French linguistics embodies a linguistic concept in its meaning. Terminological field of French linguistics meets the semantic space that is a counterpart of the French linguistics as a special subject area and includes the totality of semantic fields of general linguistic, grammatical, phonetic, phonological and lexicological terms. ____________ References • Arno,A., Lanslo, Kl. Grammatika obshhaja i racional’naja Por-Rojalja (Moskva, Progress, 1998): 93-94. • Ahmanova,O. S. «K voprosu ob osnovnyh ponjatijah metajazyka lingvistiki.» Voprosy jazykoznanija, № 5. (1964): 115-121. • Benvenist,E. Obshhaja lingvistika (Moskva, Progress, 1974), 448. • Gak,V. G. Teoreticheskaja grammatika francuzskogo jazyka (Moskva, Dobrosvet, 2000), 832. • Gijom,G. Principy teoreticheskoj lingvistiki (Moskva, Progress, 1992), 224. • Gvishiani,M. B. Jazyk nauchnogo obshhenija (voprosy metodologii): monografija (Moskva, Vysshaja shkola, 1986), 280. • Gorbunov,Ju. I. «Tezaurusnoe modelirovanie francuzskoj grammaticheskoj terminologii.» Avtoref. dis. d-ra filolog. nauk (Sankt-Peterburg, RGPU im. A. I. Gercena, 2004), 28. • Gorbunov,Ju. I. Tezaurusnoe modelirovanie metajazyka francuzskoj fonetiki i fonologii.» Nauchnoe mnenie, № 9, (2012): 46-52. • Kostjushkina,G. M. Sovremennye napravlenija vo francuzskoj lingvistike (Moskva, Librokom, 2009), 304. • Piotrovskij,R. G. Lingvisticheskaja sinergetika: ishodnye polozhenija, pervye rezul’taty, perspektivy (Sankt-Peterburg, filologicheskij fakul’tet SPbGU, 2006): 10-11. • Referovskaja,E. A. Filosofija jazyka i grammaticheskie teorii vo Francii: Iz istorii lingvistiki (Sankt-Peterburg, Izd-vo «Peterburg-XXI vek», 1996), 176. • Referovskaja,E. A. Filosofija lingvistiki Gjustava Gijoma: Kurs lekcij po jazykozaniju (Sankt-Peterburg, Akademicheskij proekt, 1997), 126. • Skrelina,L. M. «Gjustav Gijom (1883-1960) i sovremennaja lingvistika.» Vremja i prostranstvo v jazykovom predstavlenii (K 120-letiju so dnja rozhdenija Gjustava Gijoma): Tezisy dokladov mezhdunar. nauchno-praktich. konf. 23-24 oktjabrja 2003 g. (Vologda, Izd-vo «Rus’»», 2003): 3-5. • Skrelina,L. M. Istorija francuzskogo jazyka (Moskva, Vysshaja shkola, 2001), 463. • Skrelina,L. M. Teoreticheskaja grammatika francuzskogo jazyka (Sankt-Peterburg, Izd-vo RGPU im. A. I. Gercena, 2012), 386. • Ten’er,L. Osnovy strukturnogo sintaksisa (Moskva, Progress, 1988), 653. • Tomashpol’skij,V. I. Romanskoe jazykoznanie. V 2 ch. Chast’ 1 (Moskva, Izdatel’stvo Jurajt, 2018), 267. • Tomashpol’skij,V. I. Romanskoe jazykoznanie. V 2 ch. Chast’ 2 (Moskva, Izdatel’stvo Jurajt, 2018), 314. • Chernejko,L. O. «Metalingvistika: haos i porjadok.» Vestnik Moskovskogo universiteta, Serija 9. Filologija, № 5 (2001): 39-52. • Martinet,A. Eléments de linguistique générale (Paris, Armand Colin, 1970), 224. • Mounin,G. Dictionnaire de linguistique (Paris, Presses Universitaires de France, 2004), XI. • Rey-Debove,J. Le métalangage: étude linguistique du discours sur le langage (Paris, Armand Colin; Masson, 1997), 8.